Passion for Work and Well-Being of Working Adults. (June 2022) - Yukhymenko-Lescroart, Mariya A.; Sharma, Gitima
The purpose of the present study was to extend a study by Yukhymenko-Lescroart and Sharma (2019, "The Relationship Between Faculty Members' Passion for Work and Well-Being") to test the relationship between passion for work and well-being using a completely independent and much more heterogeneous sample of full-time working adults representing a wide variety of professions. Participants, who were recruited through the Amazon's Mechanical Turk website, completed several scales ( N = 297, 55.2% female, median age = 34 years), and the data were analyzed using structural equation modeling. In line with our hypotheses, results showed that harmonious passion for work contributed positively to life satisfaction, subjective happiness, awareness of purpose, altruistic purpose, and awakening to the purpose. Additionally, obsessive passion for work contributed positively to altruistic purpose and awakening to the purpose. However, the results did not support the hypothesis that obsessive passion for work contributed to the awareness of purpose.